Characterization of SiC and Al2O3 Ceramics Exposed to Nitrogen Ions from Inverse-Z Pinch Plasma Discharge - Algatti, Mauricio A. [UNESP]; Santos, Carlos N. [UNESP]; Mota, Rogerio P. [UNESP]; Campos, Elson de [UNESP]; Lucena, Emerson F.; Machida, Munemasa; Melo, Francisco C. L.; IEEE (Ieee, 2017)
Silicon carbide ceramics are used for several industry applications, such as structural coating, ballistic armor, thermal coating protection, high performance mirror substrate, catalyst supports, etc. In this work, dense SiC ceramics with different amounts of Y2O3 and Al2O3 were exposed to a plasma technique that has recently been used for material treatment called plasma expander. This process is based on the inverse Zpinch effect. Interaction of the shock waves generated by the expander with ceramic surfaces can change, for example, the wettability and the morphology of sample surface. In this paper SiC and Al2O3 ceramics were formed by using uniaxial and isostatic pressing method and sintered, respectively, at 1950 degrees C and 1600 degrees C. The SiC ceramics were produced with additive YAG in proportions of 5 wt%, 7.6 wt% and 10 wt%. On the other hand, Al2O3 ceramics were produced with 0.15 wt% MgO. All samples were sanded and polished by using the same process. The ceramics received an average of 1440 plasma pulses with discharges made at equal intervals of 20 minutes, using nitrogen as carrier gas. The use of this innovative plasma technique produced significant changes on the SiC ceramics surface. On the other hand, the alumina ceramics, that have dielectric characteristics, showed slight change after exposure to a plasma expander.
Keywords: Al2O3 ceramics; plasma expander; SiC ceramics and surface treatment